Ekbom Syndrome Management in Elderly Patients: Challenges in Risperidone Titration and Treatment Adherence - Florina Madalina Mindru; Adrian Gheorghe Bumbu; Darian Faur (Pharmacy)
Ekbom Syndrome, also known as Delusional Parasitosis (DP), is considered a rare psychiatric condition. Based on diagnostic criteria, it is characterized by the strong belief of being infested with various parasites, as well as the presence of perceptual disturbances, usually tactile and/or visual hallucinations. The syndrome can manifest idiopathically or in connection with other medical conditions and substance use. Diagnosis is challenging, as patients tend to pursue dermatological care initially. This case report describes an 81-year-old female diagnosed with Ekbom Syndrome, presenting with severe anxiety, insomnia, and persistent delusions of infestation. Initial treatment with low-dose Risperidone (2 mg/day) was ineffective, requiring a dose escalation to 4 mg/day. However, the patient’s nonadherence to follow-up limited the assessment of long-term outcomes. This case highlights key clinical challenges in elderly patients, particularly dose titration, treatment response, and adherence issues. Comparative analysis with prior case reports suggests that higher doses of Risperidone (3–6 mg/day) may be required for symptom remission, but long-term outcomes remain uncertain. Additionally, nonadherence remains a major barrier, underscoring the need for structured monitoring and caregiver involvement. These findings offer insights into antipsychotic strategies for Ekbom Syndrome, highlighting individualized pharmacotherapy, long-term follow-up, and adherence support in elderly patients.